The Black Arrow - Stevenson, Robert Louis (The Harvill Press, 1995)
The Black Arrow: A Tale of the Two Roses is an 1888 novel by the Scottish author Robert Louis Stevenson, which can be classed genre-wise as a historical adventure novel and a romance.The book started during the wars of the rose,when no citizen could shirk involvement in the conflict between the houses of the Lancaster and York.
Keywords: Juvenile literature-Fiction